2016
DOI: 10.2147/ijn.s115473
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles outperform gold nanoparticles in radiosensitizing U251 cells in vitro and in an intracranial mouse model of glioma

Abstract: Radiotherapy performs an important function in the treatment of cancer, but resistance of tumor cells to radiation still remains a serious concern. More research on more effective radiosensitizers is urgently needed to overcome such resistance and thereby improve the treatment outcome. The goal of this study was to evaluate and compare the radiosensitizing efficacies of gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs) on glioma at clinically relevant megavoltage energies. Both AuNPs and AgNPs potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 56 publications
6
86
0
1
Order By: Relevance
“…Similar results were also seen in NIH 3T3 mouse embryonic fibroblast cells, where nanosilver was observed to be contained in endosomes but not inside the nucleus, mitochondria, or golgi apparatus [63]. Nanosilver aggregates were observed in endosomes in U251 glioblastoma cells treated with citrate-coated nanosilver (15.26 nm) at a non-toxic concentration [64]. In vivo, examination of the livers of male Sprague Dawley rats treated with nanosilver (PVP-coated, 22.32 nm) via intraperitoneal injection revealed that the nanosilver was deposited in endosomes and lysosomes in Kupffer cells, and was generally in the liver cells closest to the blood vessels [65].…”
Section: Uptake Of Nanosilversupporting
confidence: 74%
“…Similar results were also seen in NIH 3T3 mouse embryonic fibroblast cells, where nanosilver was observed to be contained in endosomes but not inside the nucleus, mitochondria, or golgi apparatus [63]. Nanosilver aggregates were observed in endosomes in U251 glioblastoma cells treated with citrate-coated nanosilver (15.26 nm) at a non-toxic concentration [64]. In vivo, examination of the livers of male Sprague Dawley rats treated with nanosilver (PVP-coated, 22.32 nm) via intraperitoneal injection revealed that the nanosilver was deposited in endosomes and lysosomes in Kupffer cells, and was generally in the liver cells closest to the blood vessels [65].…”
Section: Uptake Of Nanosilversupporting
confidence: 74%
“…increase radiotherapy efficacy and prevent the development of drug-resistant tumors [44]. Another approach thoroughly studied by Rezaee, et al showed that electroporation enhances radiosensitizing effect of AuNPs in HT-29 colon adenocarcinoma cells as a result of increasing cell membrane permeability.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Nanoparticles (NP) have been used for therapy in diverse fields as a radiosensitiser [4], fluorescent labels [5], transfection vectors [6] and as drug carriers [7]. The size, shape and material composition confer advantageous properties on NP for various applications [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal nanoparticles have been utilised to enhance cytotoxicity in cancer cells using oxidising treatments such as radiation therapy [18,19]. Liu, et al, demonstrated AgNP outperforming gold nanoparticles (AuNP) in radiosensitising glioma cell line U251, where combination of AgNP and radiotherapy showed significant anti-glioma effect in vitro and in vivo in comparison to AuNP [4]. These studies resulted to multitude applications of employing NPs to cancer treatments through a vast number of strategies.…”
Section: Introductionmentioning
confidence: 99%